Assessing Nuclear Maturity: Determining which States should have Access to what Nuclear Technology - Bajema, Natasha; Nikitin, Mary Beth (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer Natasha Bajema and Mary Beth Nikitin describe how enduring weaknesses in compliance and enforcement mechanisms have been lost in the debate on nuclear proliferation and advance a new approach to proliferation threats.